An Exploration of the Potentialities of Bai-Salam as a Mode to Financing Agricultural Products in Nigeria: A Case Study of Nguru-Bade Farmers - Ahmad Doha (IAIN Syekh Nurjati Cirebon, 2024)
Lack of funding and difficult in securing loan from the bank due to absence of collateral are the major problems that detrimentally affecting the farmers of Nguru-Bade local government areas. Therefore, the overall objectives of this study are to gauge the level of awareness of the farmers of Nguru-Bade local government areas about Bai-Salam product and services and examine how Bai-Salam product can be used as best alternative in financing farmers in Nguru-Bade local government areas. The study used primary source of data (interview) to gained information for the study in order to answer the research questions and achieve the stated objectives. The study also used thematic analysis techniques to analyze the data collected through interview using focus coding techniques. The result from the study depicts out that there is lack of awareness on the Bai-Salam instrument by majority of the farmers of Nguru-Bade local government areas of Yobe state and Bai-Salam being an instrument of Islamic financial institutions can play a vital role in financing farmers deficit in the areas from planting up to harvesting period.